1996
DOI: 10.1101/lm.3.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Training in the Morris water maze occludes the synergism between ACPD and arachidonic acid on glutamate release in synaptosomes prepared from rat hippocampus.

Abstract: In~oducUonWe report here that release of glutamate, inositol phospholipid metabolism, and protein kinase C (PKC) activity are increased in synaptosomes prepared from hippocampi of rats that had been trained in a spatial learning task. In hippocampi obtained from animals that were untrained, activation of the metabotropic glutamate receptor by the specific agonist trans, l.amino.cyclopentyl, l ,3.dicarboxylate (ACPD) increased release of glutamate but only in the presence of a low concentration of arachidoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…Our results thus provide support for earlier observations that spatial learning is accompanied by an increase in the ability of synaptosomes from the dentate gyrus to release glutamate in response to depolarization (Richter-Levin et al 1995;McGahon et al 1996). Partial training in the spatial task (1 Block) or training with a visible platform resulted in partial, rather than complete, occlusion of tetanus-induced enhancement of glutamate release (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results thus provide support for earlier observations that spatial learning is accompanied by an increase in the ability of synaptosomes from the dentate gyrus to release glutamate in response to depolarization (Richter-Levin et al 1995;McGahon et al 1996). Partial training in the spatial task (1 Block) or training with a visible platform resulted in partial, rather than complete, occlusion of tetanus-induced enhancement of glutamate release (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…There is evidence that learning is associated with a similar increase in glutamate efflux in the dentate gyms. Laroche and his colleagues found an NMDA receptor-dependent increase in depolarization-induced release of radiolabeled glutamate in slices from the dentate gym of conditioned as compared to pseudoconditioned animals in a food-motivated lever-pressing task Redini-Del Negro and Laroche 1993), and more recently, increases in both endogenous (Richter-Levin et al 1995) and radiolabeled (McGahon et al 1996) glutamate efflux have been reported following training in a spatial learning task, the Morris water maze.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, an increase in glutamate release has been reported following both LTP (e.g. Dolphin et al 1982, Bliss et al 1986; but see Aniksztejn et al 1989, Diamond et al 1998, Lüscher et al 1998 and watermaze learning (Richter-Levin et al 1995, McGahon et al 1996. Richter-Levin et al (1997) trained rats in a spatial watermaze task for varying numbers of trials, then induced LTP in vivo on one side of the brain and finally examined veratridine-induced glutamate release in synaptosomes prepared from the hippocampus of the trained animals.…”
Section: Exploration and Learning Induce Changes In Hippocampal Fieldmentioning
confidence: 96%
“…Increased glutamate release has been reported after both LTP (Dolphin et al, 1982;Bliss et al, 1986; but see Aniksztejn et al, 1989;Diamond et al, 1998;Lüscher et al, 1998) and water maze learning (Richter-Levin et al, 1995;McGahon et al 1996). In a subsequent study, Richter-Levin et al (1998) trained rats in a water maze task and then induced LTP on one side of the brain in vivo, before finally examining veratridine-induced glutamate release in hippocampal synaptosomes.…”
Section: Changes In Glutamate Releasementioning
confidence: 96%